UMPSA strengthens research collaboration with Imperial College London - Nur Ezzati, Mohd Nasir (UMPSA, 2025)
LONDON, 8 September 2025 - A delegation from Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA), led by the Director of UMPSA Global, Associate Professor Dr. Herma Dina Setiabudi, made an official visit to the Department of Chemical Engineering, Imperial College London, to strengthen academic and research collaboration with one of the world’s leading research universities.